PERANCANGAN KURSI OPERATOR COLD SHEAR DENGAN PENDEKATAN ERGONOMI ANTROPHOMETRI DAN ANALYTICAL HIERARCHY PROCESS DI PT. ISPAT PANCA PUTERA - Arif Setiawan (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2018)
Working system within a company must be experiencing a complaint is found, through the study found about cold shear operator complaint against a chair design makes operator experience pain in certain body parts. In this problem, how to overcome it so that the performance can be maximized.The researcher used the ergonomic approach and the selection of alternative designs antrophometri seats through AHP (Analytical Hierarchy Process). With this approach can determine how the direction in designing the seat with the best design and choose the best seats alternative. The methods used for data processing using AHP (Analytical Hierarchy Process). Stages in the method of AHP begins the process of defining the problem, creation of hierarchy structure that begins with a common goal, followed by criteria and of alternatives, Make matrix pairwise comparisons, normalize the data, calculation the eigenvalues vector and tested for consistency, calculate the eigen vector of each pairwise comparison matrices, test the consistency of the hierarchy. If it does not comply with CR <0.100 then the assessment should be repeated.The results found that there are four design alternatives chairs and fourth alternative was selected as the best design alternatives through the analysis of decision-making with AHP method.By optimizing the operator's seat facility, will certainly enhance good performance and reduce fatigue and pain experienced operators during this cold shear.